Analisis Pemahaman Konsep pada Materi Perubahan Wujud Zat dengan Menggunakan Instrumen Three Tier Test Siswa SMA Negeri 1 Lore Utara - Risky Eka Saputra; Marungkil Pasaribu; Syamsu Syamsu (Universitas Tadulako, 2021)
This study aims to describe the understanding of students at SMA Negeri 1 Lore Utara on the concept of changing the state of matter. Subjects and respondents in this study were 29 students of SMA Negeri 1 Lore Utara. The research instrument used was a concept understanding test in the form of multiple choice reasoned accompanied by a level of confidence in answering questions (tree tier test). The test instrument used was 25 number of questions. The test result data is then analyzed to determine the percentage of understanding scientific concepts, misconceptions, and not understanding concepts. Based on the results of the research data analysis, the percentage of the category not understanding the concept of 44.28%, understanding scientific concepts 16.97%, and misconceptions of 38.76%. From the results of the study, it can be concluded that the understanding of the concept of changing the state of matter in the students of SMA Negeri 1 Lore Utara is still very low.